Comparison of the 2017 ACC/AHA Hypertension Guideline with Earlier Guidelines on Estimated Reductions in Cardiovascular Disease - Bundy, Joshua D. (Curr Hypertens Rep, 2019)
PURPOSE OF REVIEW: To review the recommendations of the 2017 American College of Cardiology/American Heart Association hypertension guideline and to compare it with previous guidelines on potential cardiovascular disease (CVD) and mortality risk reductions. RECENT FINDINGS: Compared with previous guidelines, the 2017 hypertension guideline increased the prevalence of hypertension and the number of adults recommended for antihypertensive therapy in the US population. Based on data from recent analyses, the new guideline effectively directs antihypertensive therapy toward individuals at higher CVD risk. Two recent analyses using US national data estimated that implementation of the 2017 hypertension guideline could further reduce hundreds of thousands of CVD events and deaths compared with previous guidelines. However, the new guideline might increase the number of adverse events. The new guideline also improves the number of individuals needed to treat to prevent CVD events and deaths, suggesting implementation is cost-effective. SUMMARY: Implementation of the 2017 hypertension guideline is projected to substantially reduce CVD events and deaths in the US but might increase the number of adverse events. Future research is needed to implement and scale up effective, equitable, and sustainable strategies for applying the new guideline in daily clinical practice.